(untitled) (Research, Society and Development, 2021)
Objective: know the self-care of men and women with Diabetes Mellitus type 2. Methodology: Qualitative and descriptive study. Data were collected between July 2019 to august 2019 by semi-structured interviews. 14 people have participate, seven of them were men and seven women with diabetes type 2 treated in the Integrated Center of diabetes on a University Hospital. Results: The analysis found 4 categories named “Knowledge about what is self-care face to DM2 e family participation”; “General aspects of self-care about DM2”; “Eat behavior versus self-care”;” The Life routine versus the physical activity”. Similarities behaviors were found between men and women, as such as care with diet, with feet and medication, beyond performing physical activities. In the last year, was checked that women are more involved in house tasks and take care of family members, that compared to men, reduce the practice of physical activities, highlighting the disparities between genders. Final considerations: To improve the people self-care with diabetes, is necessary a bigger commitment and consciousness of themselves about their health with life chance style. This process can be facilitated by health professional interventions, in special of nursing, concerning to individual health, taking on consideration gender questions relevant that could affect the self-care.